New perspectives in diagnosis and risk stratification of non-ischaemic dilated cardiomyopathy. (26th April 2023) - Pio Loco detto Gava, Carola; Merlo, Marco; Paldino, Alessia; Korcova, Renata; Massa, Laura; Porcari, Aldostefano; Zecchin, Massimo; Perotto, Maria; Rossi, Maddalena; Sinagra, Gianfranco
Abstract: Dilated cardiomyopathy is a primitive heart muscle condition, characterized by structural and functional abnormalities, in the absence of a specific cause sufficient to determine the disease. It is, though, an 'umbrella' term that describes the final common pathway of different pathogenic processes and gene–environment interactions. Performing an accurate diagnostic workup and appropriate characterization of the patient has a direct impact on the patient's outcome. The physician should adapt a multiparametric approach, including a careful anamnesis and physical examination and integrating imaging data and genetic testing. Aetiological characterization should be pursued, and appropriate arrhythmic risk stratification should be performed. Evaluations should be repeated thoroughly at follow-up, as the disease is dynamical over time and individual risk might evolve. The goal is an all-around characterization of the patient, a personalized medicine approach, in order to establish a diagnosis and therapy tailored for the individual patient.